Silk and steel: A gendered approach to career and life by upper echelon women executives in the hospitality and tourism industry in China. (August 2021) - Fan, Xiangli; Im, Jinyoung; Miao, Li; Tomas, Stacy; Liu, Hailing
Abstract: This qualitative study represents one of the early attempts to uncover the lived experience of thriving of top female leaders in the tourism and hospitality industry in China. Based on the narratives of 21 women executives in the hospitality and tourism industry in China, this study reveals that upper echelon (top management) females thrive by taking a gendered approach to life and career in a cultural environment with a strong Confucian tradition. This research systematically explored the unique gendered orientations and strategies these women executives used to achieve optimal functioning, as manifested in their thriving in both life and career. They acknowledge gender differences, embrace female qualities rather than deny them, and leverage these qualities to their advantage. The study findings offer significant theoretical and practical implications by illuminating a thriving perspective of the career advancement of women. Highlights: This study uncovers the lived experience of thriving of women executives in the hospitality and tourism industry in China. This study reveals that upper echelon females thrive in their career by taking a gendered approach to life and career. The results indicate women executives perform the required professional and familial roles in optimal gendered functioning. The study suggests they acknowledge gender differences, embrace female qualities and leverage them to their advantage. The cultural context of Confucianism provides a unique lens to understand career advancement of Chinese women executives.